Peningkatan Kualitas Layanan Rumah Makan Melalui Digitalisasi dengan Metode Design Thinking - Hikmah, Nabillah Nur; Prabowo, Fajar Sidiq Adi (Universitas Proklamasi 45, 2025)
Digitalization has significantly impacted the culinary industry, necessitating that businesses adapt to remain competitive. Rumah Makan and Café Saung Bodeman face service challenges, including manual reservations, limited menu information, and inefficient operations. This study aims to design a digital service program using the Design Thinking method through five stages: empathize, define, ideate, prototype, and test. A qualitative approach with interviews and observations was conducted to explore user needs from both consumers and employees. The research produced two interactive website prototypes: one for consumers (online reservations, menu ordering, estimated processing time, and menu availability) and one for employees (a dashboard for reservation management, menu and seating updates, and input reservations). Usability testing with the System Usability Scale (SUS) involving 12 respondents showed that both prototypes achieved acceptable scores with good user satisfaction. The results show that the proposed digital solution effectively addresses service issues and can improve Saung Bodeman's competitiveness in the digital era.